Response of (Kopsia arborea Blume) Seed Germination to Rhizosphere Microbial Treatment - Muhammad Ridwan; Arum Sekar Wulandari; Yunik Istikorini (Jurnal Penelitian Pendidikan IPA, 2026)
Kopsia arborea Blume is a plant species with high bioactive potential, yet its cultivation remains underdeveloped. One of the primary challenges in generative propagation is the low viability and slow seed germination rate. This study aims to analyze the effect of generative materials and rhizosphere microbes on the germination of Kopsia seeds. The generative materials used include whole fruits and fruit embryos of Kopsia. The rhizosphere microbes applied consist of a mixture of Trichoderma sp., Bacillus sp., Pseudomonas sp., and Azospirillum sp. The generative materials were cultivated in sand media over a two-month observation period. The observed parameters included the germination process, germination capacity, maximum growth potential, mean germination time, germination rate, vigor index, plant height, seedling length, total fresh weight, total dry weight, and shoot-root ratio. The treatment of generative materials significantly influenced germination capacity, mean germination time, germination rate, total fresh weight, total dry weight, and shoot-root ratio. Microbial applications affected germination capacity, mean germination time, maximum growth potential, vigor index, and seedling length. Overall, both whole fruits and embryos of kopsia are suitable for generative propagation. However, microbial applications are only necessary when propagation is conducted using whole fruits.